Inter‐Organizational Learning in Supply Chains: A Focus on Logistics Service Providers and Their Customers. Issue 2 (20th May 2014) - Manuj, Ila; Omar, Ayman; Pohlen, Terrance L.
<x xml:space="preserve">Abstract</x> The learning process between supply chain entities is explored from the perspective of senior third‐party executives. Through grounded theory, a theoretical framework emerged that extends our understanding of learning within a supply chain by identifying the major constructs and learning stages comprising the basic social process of inter‐organizational learning. This framework provides significant insights into the complex process employed in a supply chain to share, disseminate, and store information; co‐create knowledge; and to derive a competitive advantage.